Honokiol suppresses 2, 6-dinitrochlorobenzene-induced atopic dermatitis in mice. (10th May 2022) - Lee, Ju-Hyun; Im, Dong-Soon
Abstract: Ethnopharmacological relevance: Magnolia officinalis constitutes a traditional Korean medicine used for the treatment of atopic dermatitis, and honokiol is an active diphenyl compound present in Magnolia officinalis . Aim of the study : The aim of the study was to investigate the therapeutic effects of honokiol on atopic dermatitis in vivo . Materials and methods: The therapeutic effects of honokiol were evaluated in a 2, 4-dinitrochlorobenzene (DNCB)-induced atopic dermatitis model. Results: Administration of honokiol (10 mg/kg) significantly suppressed mast cell accumulation and inflammation induced by DNCB in skin tissues. Moreover, DNCB-induced increases in serum immunoglobulin E levels were reversed by honokiol treatment. In addition, DNCB-induced elevation of inflammatory cytokines (interleukin (IL)-4, IL-13, IL-17, and interferon-γ) in the skin and lymph nodes was significantly ameliorated by honokiol administration. Furthermore, the increase in lymph nodes sizes induced by DNCB treatment was reduced by honokiol administration. Conclusion: DNCB-induced atopic responses in the ears and lymph nodes were significantly suppressed by honokiol treatment. These results suggested that honokiol is a potential therapeutic agent for atopic dermatitis. Graphical abstract: Image 1